EVALUASI PENERAPAN SISTEM PENGENDALIAN INTERNAL PEMBELIAN KREDIT GUNA MENINGKATKAN KETEPATAN ATAS SUPPLY CHAIN PADA PT. WELCO: Indonesia - Bella Juliany Putri Mulyono; Revi Arfamaini (Bajang Institute, 2023)
In the current post-pandemic era, companies in Indonesia are setting strategies to achieve profits by carrying out various product innovations and selling the highest quality products in order to expand the target market, especially for manufacturing industry companies. The manufacturing industry is one of the largest industries in Indonesia and is the main driving force for national economic growth. Manufacturing companies obtain raw materials by conducting purchasing activities. In order to achieve this goal, an internal control system is needed for credit purchasing activities so that operations and supply chains in manufacturing companies run effectively and efficiently. PT. WELCO is a manufacturing company located in Surabaya and engaged in the Food and Beverages sector. This study evaluates the application of internal control based on COSO theory related to five components namely, control environment, risk assessment, control activities, information and communication, and supervision. Descriptive qualitative methodology is the research technique used. Utilizing observation, interview, documentation, and triangulation techniques, the type of data used is qualitative data. Primary data is the data's source. The results of this research show that the internal control system of PT. WELCO is still inadequate due to the absence of SOP, unclear separation of duties and responsibilities, unclear organizational structure, lack of risk assessment of supply chain and debt repayment, incomplete supporting documents for credit purchasing activities, and lack of data disclosure regarding terms payments and lead times from suppliers to inter-divisions related to credit purchasing activities.